GASTRONOMIC DISHES AS SOCIO-CULTURAL REPRESENTATION: AN ETHNOGASTRONOMIC STUDY IN THE OSING BANYUWANGI COMMUNITY, EAST JAVA - Nurul Farikhatir Rizkiyah; Andika Kuncoro Widagdo; Rendra Lebdoyono; Asrul Bahar; Nugrahani Astuti (Bajang Institute, 2025)
This study examines the gastronomy of the Osing community in Banyuwangi as a socio-cultural representation that includes symbolic, spiritual, social, and ecological dimensions. The Osing people as the indigenous people of Banyuwangi have a culinary tradition that not only serves as a fulfillment of food needs, but also as a medium of cultural expression, ethnic identity, and guardian of local wisdom. Globalization and modernization affect the consumption patterns of the younger generation, so that traditional culinary values have the potential to be degraded. Through a qualitative approach with ethnographic methods, including participatory observation, in-depth interviews, and documentation. This research was conducted in Kemiren Village as the center of Osing culture. The results of the study show that ritual dishes such as pecel pitik, tumpeng sewu, and tumpeng songo contain the philosophy of human harmony with nature, spiritual relationship with ancestors, and social solidarity through the practice of mutual cooperation. Local ingredients and traditional processing techniques reflect the ecological knowledge of the Osing people that is in harmony with the principles of sustainable gastronomy. In the context of tourism, Osing culinary plays a strategic role as the main attraction, but at the same time faces the challenge of cultural commodification due to the development of the tourism industry. The community-based gastronomic tourism model is a solution to maintain cultural authenticity while providing economic benefits for local communities. This research confirms that Osing gastronomy is a holistic knowledge system that integrates cultural, ecological, and economic aspects, and contributes to the achievement of the Sustainable Development Goals (SDGs). These findings are expected to be the basis for the development of traditional culinary preservation policies and the strengthening of sustainable tourism in Banyuwangi.